2019
DOI: 10.1016/j.aca.2018.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty estimation and misclassification probability for classification models based on discriminant analysis and support vector machines

Abstract: Uncertainty estimation and misclassification probability for classification models based on discriminant analysis and support vector machines,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…1). While widely employed in the chemistry community,19,39,40,42,43 ensembles increase the model training effort in proportion to the number of models used (typically an order of magnitude, ESI Text S1†). Although this additional effort may be practical for some models ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…1). While widely employed in the chemistry community,19,39,40,42,43 ensembles increase the model training effort in proportion to the number of models used (typically an order of magnitude, ESI Text S1†). Although this additional effort may be practical for some models ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The kernel function (in this case, the radial bases function (RBF)) transforms the input spectral data into a feature space that maximises the margin of separation between the classes. Although more powerful than LDA or QDA for classification, SVM is more susceptible to overfitting 24 .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, each dimensionality reduction algorithm suggests a different set of variables to be used in SVMs, which can result in controversy. Recent studies ( [15], [18], and [24]) have shown that the boostrap procedure may have a number of benefits in classification problems, like reducing a model's uncertainty or finding the appropriate number of clusters in the k-nearest neighbor.…”
Section: E a R L Y B I R Dmentioning
confidence: 99%